1987
DOI: 10.1021/ac00151a020
|View full text |Cite
|
Sign up to set email alerts
|

Detection of aerosol formation in the effluent of a supercritical fluid chromatograph

Abstract: Supercritical fluid techniques continue to grow in importance in analytical chemistry, especially supercritical fluid chromatography (1). Accompanying this growth is the development of postcolumn detection methods, including flame ionization detection (2,3), inductively coupled plasma emission (4), mass spectrometry (5, 6), and supersonic jet spectroscopy (7-9). In each of these detection methods, the behavior of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Goates et al [129,131] observed that aerosol formation occurred when a phase boundary was crossed (a dew point line) during isenthalpic decompression of the flow into the restrictor. Liquid droplets (solvent enriched with solute) condense after the dew point line is crossed.…”
Section: Phase Transitions In the Injector And Restrictormentioning
confidence: 99%
See 1 more Smart Citation
“…Goates et al [129,131] observed that aerosol formation occurred when a phase boundary was crossed (a dew point line) during isenthalpic decompression of the flow into the restrictor. Liquid droplets (solvent enriched with solute) condense after the dew point line is crossed.…”
Section: Phase Transitions In the Injector And Restrictormentioning
confidence: 99%
“…If the decompression zone is extended (as in a linear restrictor), these aerosol droplets coalesce into larger aggregates. Goates et al [129,131] reported a threshold temperature above which aerosol formation did not occur (the dew point line is not crossed). Also, aerosol formation was associated with erratic sample flow.…”
Section: Phase Transitions In the Injector And Restrictormentioning
confidence: 99%
“…Other authors (117,118) have previously reported spiking due to the use of linear restrictors in connection with SFC. Spiking occurs due to the formation of aerosols during fluid decompression (119).…”
Section: Instrumentation For Secondary Flow Chromatographymentioning
confidence: 99%
“…Such clusters, which spoil spectral selectivity, are prone to form with the polyatomics employed as SF eluents or carriers (4). Finally, decompression of the SF carrier in the throat of the nozzle can cause it to condense if the nozzle temperature is not high enough (10,11) and can cause nonvolatile analyte to precipitate, especially with an extended restrictor (4,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Anderson and Johnston (16) were also unable to transport nonvolatile molecules into the jet through a sheath-flow nozzle, but they made an enlightening study of the performance of the nozzle with naphthalene in SF and liquid carriers. Their work along with our studies of direct SF expansions (4,10) has led to a sheath-flow nozzle design which delivers all the hoped-for benefits except for sample focusing and has allowed SJS to be coupled to capillary SFC (8). In this paper investigations into the parameters that govern the performance of the nozzle are reported.…”
Section: Introductionmentioning
confidence: 99%